Discussion - Of Mr. Baker's Paper on Stock-Distribution and its Relation to the Life of a Blast-Furnace Lining (see p. 244) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1905)
Edward A. UehlinG, New York City (communication to the Secretary*):—Mr. Baker's paper is one that brings up a subject of great importance, and if full statistics could be collectecl of the number of furnace-linings ruined by reason of bad distribution by skip-hoists, it would be found an astonishing array. Unfortunately a universal remedy has not yet been found. The fact that Mr. Baker has apparently succeeded in overcoming the trouble at Sydney, is no guarantee that the same remedy applied at another plant, where very different or even slightly different conditions prevail, mould cure the trouble. That it requires but a slight continuous difference of penetrability in the column of the descending stock of one section, over another, to produce channeling, is clearly demonstrated by Mr. Baker's experiments, by which he reversed the channeling from front to rear instead of remedying the trouble. Every change in the physical make-up of the charge necessarily requires a specific adjustment; even supposing this feasible, the regular working of the furnace is by no means assured, because with the high pressures now customary, the tendency of the ascending gases to plow their way through in a direct course, prevails, and having once opened up a passage, they will persist and cause trouble. Homogeneous filling-, hard driving and regularity of working are incompatible. The higher the furnace, the greater the